A Comparative Analysis of the Determinants of Executive Compensation between Canadian and U.S. Firms - Magnan, Michel; St-Onge, Sylvie; Thorne, Linda (Relations industrielles / Industrial Relations, 1995)
This study attempts to identify determinants of executive compensation in Canada while comparing how they differ between Canada and the United States. Results suggest that firm size, firm performance, and firm ownership structure all determine executive compensation in Canada. However, several differences between the determinants of executive compensation in Canada and the U.S. are identified.